A policy rooted in Mother Earth and from the heart. Keys to a policy of dignity - GUTIÉRREZ LUNA, Diana (Utopía y Praxis Latinoamericana, 2024)
Our objective is to pay tribute to the invaluable figure of the master Carlos Walter Porto-Gonçalves, who taught us to look at and get involved in reality from the critical thinking and the heart. It also shows a weaving of threads of experiences shared in Chiapas, Mexico with women’s collectives. It also honors the thirty years of experience of the Zapatista Army of National Liberation (EZLN), whose territorial and organizational expressions have provided and continue to provide valuable learning and unlearning to those of us who continue to organize for worlds of life without exploitation, contempt, dispossession and violence. From a participatory and committed advocacy methodology, they seek to open questions and imaginaries to rethink politics beyond the established canons, inspired by these experiences. The results invite to collectively test and learn new practices rooted in Mother Earth, rooted in the territories, guided by rebellious dignity and with a community vocation.